A Situational Study of Inpatient Department Staffs Confronting Personnel Elevator Problems at Srinagarind Hospital, August 2014 - Na Nakhonphanom, Thanaphop; Yuthawong, Sopiruch; Sittirach, Nunsita; Srimanta, Phongwarong; Mattaya, Sarat; Mala, Onanong; Chaiyuttho, Anupap; Pinitsoontorn, Somdej; Ratanasiri, Amornrat (Srinagarind Medical Journal, 2014)
Background and objective: Although elevators are one of the safest form of transportation, their problems may affect both physical and mental health. 265 elevator problems (approx. 22 times per month) were reported in 2013 and 8 were reported in July, 2014, therefore this descriptive study was attempted to find the prevalence of inpatient department staffs confronting personnel elevator problems,and impacts on working performance and mental health, confidentiality and knowledge of safely using elevator. Method: The study population was 281 from 994 inpatient department staffs regularly working in August, 2014 selected by systematic sampling. Self-administered questionnaire including demographic data, elevator using and effects. SPSS-PC 17.0 used to analyze the proportion, 95%CI, median and interquartile range. Results: Response rate was 80.4% (226/281). The prevalence of inpatient department staffs confronting personnel elevator problems was 75.2%. The three most frequent problems are door operation problems (64.2%, 95%CI 57.5, 70.3), electrical noise generation and mechanical vibration (55.8%), elevator stuck (51.8%). The least frequent problem is elevator fall (9.7%). 8% of the staffs have knowledge of safely using elevator. Moreover the problems had 31.9% of them be late, delay the period of a service. They also caused panic attack and anxiety. Conclusion: The most prevalent elevator problems are door operation problem and electrical noise generation and mechanical vibration, respectively. The least one is elevator fall. The problems had the staffs be late, delay the period of a service and caused panic attack and anxiety.